Spreading dynamics based key nodes identification in inter-domain routing system - Huihu ZHU; Han QIU; Junhu ZHU; Ziyi ZENG (网络与信息安全学报)
The inter-domain routing system is a critical infrastructure of the Internet and it is of great significance to protect the key nodes of inter-domain routing system.The key nodes identified by the existing methods can not reflect the importance of the nodes on the cascading failure process.The method of key nodes identification is proposed basing on spreading dynamics.A node importance evaluation model based on DDF-CFM model is proposed.,which could takes the failure effect caused by load redistribution and UPDATE messages propagation into account after node fails.The experiments turn out that the accuracy of this method is at least 7.3% higher than that of exist ing methods.And the experimental results show that in the scale of 10000 nodes,the failure of only 5 key nodes will lead to large-scale cascade failure of inter-domain routing systems.